Thiamine-Mediated Cooperation Between Auxotrophic Rhodococcus ruber ZM07 and Escherichia coli K12 Drives Efficient Tetrahydrofuran Degradation - Huang, Hui; Qi, Minbo; Liu, Yiming; Wang, Haixia; Wang, Xuejun; Qiu, Yiyang; Lu, Zhenmei (Frontiers in Microbiology, 2020)
Tetrahydrofuran (THF) is a universal solvent widely used in the synthesis of chemicals and pharmaceuticals. As a refractory organic contaminant, it can only be degraded by a small group of microbes. In this study, a thiamine auxotrophic THF-degrading bacterium, Rhodococcus ruber ZM07, was isolated from an enrichment culture H-1. It was cocultured with Escherichia coli K12 (which cannot degrade THF but can produce thiamine) and/or Escherichia coli K12ΔthiE (which can neither degrade THF nor produce thiamine) with or without exogenous thiamine. This study aims to understand the interaction mechanisms between ZM07 and K12. We found that K12 accounted for 30% of the total when cocultured and transferred with ZM07 in thiamine-free systems; in addition, in the three-strain (ZM07, K12, and K12ΔthiE) cocultured system without thiamine, K12ΔthiE disappeared in the 8th transfer, while K12 could still stably exist (the relative abundance remained at approximately 30%). The growth of K12 was significantly inhibited in the thiamine-rich system. Its proportion was almost below 4% after the fourth transfer in both the two-strain (ZM07 and K12) and three-strain (ZM07, K12, and K12ΔthiE) systems; K12ΔthiE’s percentage was higher than K12’s in the three-strain (ZM07, K12, and K12ΔthiE) cocultured system with exogenous thiamine, and both represented only a small proportion (less than 1% by the fourth transfer). The results of the coculture of K12 and K12ΔthiE in thiamine-free medium indicated that intraspecific competition between them may be one of the main reasons for the extinction of K12ΔthiE in the three-strain (ZM07, K12, and K12ΔthiE) system without exogenous thiamine. Furthermore, we found that ZM07 could cooperate with K12 through extracellular metabolites exchanges without physical contact. This study provides novel insight into how microbes cooperate and compete with one another during THF degradation.